2022
DOI: 10.2147/ijgm.s355043
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Diagnostic and Prognostic Value of hsa_circ_0084927 and Analysis of Associated ceRNA Network in Colorectal Cancer

Abstract: Object This study aims to analyze the differentially expressed circRNA in colon adenocarcinoma (COAD) and evaluate its diagnostic and prognostic value. Analyze associated circRNA-miRNA-mRNA network in COAD. Methods and Materials Real-time quantitative PCR (RT-PCR) was used to verify differentially expressed circRNA in COAD tissues and cells; Receiver operator characteristic (ROC) and Cox regression analysis were used to evaluating its diagnostic and prognostic value; Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…NcRNAs has been used as prognostic markers in colon cancer. A recent study found that has_circ_0084927 has prognostic value in colorectal cancer and has an endogenous competition mechanism [ 25 , 26 ]. The effect of KCNQ1OT1 on lncRNAs in the development of colon cancer has been confirmed in several studies [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…NcRNAs has been used as prognostic markers in colon cancer. A recent study found that has_circ_0084927 has prognostic value in colorectal cancer and has an endogenous competition mechanism [ 25 , 26 ]. The effect of KCNQ1OT1 on lncRNAs in the development of colon cancer has been confirmed in several studies [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This pattern is reversed in the HCT116 cell line samples from project PRJNA748887 [40], with the tRFs of lengths 29 and 31 nts now being more abundant. This pattern is absent in the cell line samples from projects PRJNA784982 [41], PRJNA595962 [42], and PRJNA789176 [43].…”
Section: The Abundances Of Different-length 5 -Trhs Depend On Contextmentioning
confidence: 91%